From specialized web corpora of tourism to a learner’s dictionary - Srdanović, Irena (2020)
This paper presents the two approaches used in creating specialized web corpora of Croatian tourism in Japanese for their usage in building a specialized learners’ dictionary. Both approaches use the WebBootCat technology (Baroni et al. 2006, Kilgarriff et al. 2014) to automatically create specialized web corpora. The first approach creates the corpora from the selected seed words most relevant to the topic. The second approach specifies a number of web pages that cover tourism-oriented information on specified regions, cities, and sites in Croatia available in Japanese, which are then used for web corpora creation inside the Sketch Engine platform. Both approaches provide specialized web corpora small in size, but quite useful for lexical profiling in the specific field of tourism. In the process of dictionary creation, the second approach has proven to be especially useful for the selection of lexical items, while both approaches have proven to be highly useful for the exploration and selection of authentic examples from the corpora. The research exposes some shortcomings in Japanese language processing, such as errors in the lemmatization of some culturally specific terms and indicates the need to refine existing language processing tools in Japanese. The Japanese-Croatian bilingual learner’s dictionary (Srdanović 2018) is currently in the pilot phase and is being used and built by learners and teachers through the open-source dictionary platform Lexonomy (Mechura 2017). In addition to the fact that work on the bilingual dictionary is useful as a means for training students in language analysis and description using modern technologies (e.g. corpora, corpus query systems, dictionary editing platform), the dictionary is also important in educating new personnel capable of working in tourism using the Japanese language, which is strongly needed.
U ovom radu predstavljena su dva pristupa u stvaranju specijaliziranih mrežnih korpusa o hrvatskom turizmu na japanskome jeziku za potrebe izrade specijaliziranoga dvojezičnog japansko-hrvatskog rječnika za učenike japanskoga jezika. Oba pristupa koriste se tehnologijom WebBootCat unutar platforme Sketch Engine za automatsko stvaranje specijaliziranih mrežnih korpusa (Baroni i dr. 2006, Kilgarriff i dr. 2014). Prvi pristup stvara korpus iz odabranih riječi, odn. polaznih pojmova (eng. seed words) koje su najrelevantnije za temu. Drugi pristup skuplja brojne mrežne stranice sa sadržajima o turizmu u određenim regijama, gradovima i mjestima u Hrvatskoj napisanim na japanskome jeziku, koje se zatim upotrebljavaju za stvaranje mrežnih korpusa. Oba pristupa pružaju specijalizirane internetske korpuse koji su, bez obzira na malu veličinu, korisni za profiliranje leksika u određenome području, u ovome slučaju u području turizma. U procesu stvaranja rječnika drugi se pristup pokazao osobito korisnim za odabir natuknica, dok su se oba pristupa pokazala vrlo korisnim za istraživanje i odabir autentičnih primjera iz korpusa. Uočeni su i određeni nedostatci u jezičnoj obradi podataka na japanskome jeziku, npr. pogreške u lematizaciji nekih pojmova i naziva svojstvenih određenoj kulturi te je ukazano na potrebu za usavršavanjem postojećih alata za jezičnu obradu podataka na japanskome jeziku. Japansko-hrvatski dvojezični rječnik namijenjen učenicima japanskoga jezika trenutačno je u eksperimentalnoj fazi te se učenici i nastavnici njime koriste i grade ga s pomoću otvorene platforme za izradu mrežnih rječnika Lexonomy (Mechura 2017).
Bibliografske bilješke uz tekst ; bibliografija: str. 1080-1082.
Summary ; Sažetak.
Keywords: Rječnici -- Specijalizirani rječnici -- Hrvatski jezik -- Japanski jezik -- Mrežni korpusi -- Turizam